APPLICATION OF ACCOUNTING INFORMATION SYSTEMS IN THE COMPANY PT. RCK SORUM MOTOR - Oon Feriyanto; Herni Yuliantika; Bilal Abdillah; Rasya Fitriyani N.A; Ichsan Abdul R; Sandria Ridhatullah Januar Akbara (Politeknik Siber Cerdika Internasional, 2023)
This research focuses on sales accounting information system problems which play a role in supporting the smooth running of the sales process. The problems that occur can be overcome with an accounting information system. In carrying out its activities, companies really need clear and relevant information to make decisions. One of the information needed is company accounting information that can support the company's survival. The Accounting Information System (AIS) is a technological framework that integrates accounting processes with information technology to increase efficiency and accuracy in managing financial data. This research explores the role of AIS in the modern organizational context, focusing on its success in providing relevant, timely and reliable accounting information. The analysis covers aspects of technology implementation, system integration, data security, and its impact on managerial decision making. The findings of this research can provide important insights for companies looking to optimize their AIS to support growth and sustainability.